EFFECTS OF SUSTAINABLE CONSTRUCTION SITE PRACTICES ON ENVIRONMENTAL PERFORMANCE OF CONSTRUCTION PROJECTS IN NIGERIA - Onubi, Hilary Omatule; Yusof, Nor Aini; Hasan, Ahmad Sanusi (PLANNING MALAYSIA, 2020)
There are growing calls for construction site activities to be carried out in a sustainable manner. The reason for these calls is not far-fetched in view of the enormous impact such construction activities have on the natural environment. The objective of this study is to examine the effects of green construction site practices on environmental performance of construction projects in Nigeria. The effects of three green construction site practices namely waste management, materials management and energy management on environmental performance were analysed. 168 questionnaires were administered to site managers and project managers from “class A” contractors. The data were analysed using partial least squares-structural equation modelling. The results indicate that waste management has an insignificant impact on environmental performance, while materials management and energy management have positive effects on environmental performance. The results imply that not all sustainable construction site practices lead towards the attainment of environmental performance. The study has both theoretical and practical implication that helps policy makers and contractors to better understand the relationships that exists between these variables of sustainable construction site practices as well as environmental performance. This is essential in order to come out with a better plan for their projects and formulation of appropriate policies.